The specificity for the correlation between viscera and somato in chronic stable angina pectoris patients and healthy controls: An assessor-blinded and comparative trial - Yongliang Jiang; Xiaoyu Li; Xiaofen He; Hantong Hu; Yajun Zhang; Xiaomei Shao; Jianqiao Fang (PLoS ONE, 2025)
Background Although the relationship between viscera and somato remains unclear, a deeper comprehension of the relationship will maximize the diagnostic and therapeutic benefits. Therefore, this study was conducted to explore the specificity of visceral-somatic associations in the pathological state of chronic stable angina pectoris (CSAP). Methods 40 individuals with CSAP participated in the study, while 40 individuals in the healthy control group were age-matched healthy individuals. Four distinct somatic locations dispersed along the heart and lung meridians were subjected to laser doppler flowmetry, infrared thermography, and functional near-infrared spectroscopy in order to assess (1) perfusion unit (PU), (2) temperature, and (3) regional oxygen saturation (rSO2). These three outcomes represented the somatic sites’ microcirculatory, thermal, and metabolic properties. Results Regarding the microcirculatory characteristics, PU at the somatic sites of the heart meridian (Shenmen(HT7)/Shaohai(HT3)) in the CSAP group substantially increased (P < 0.05) compared to the healthy control group, while there was no statistically significant difference in PU at the somatic sites of the lung meridian between the two groups. Regarding the thermal characteristics, compared with the healthy control group, the temperature of the somatic sites of the heart meridian (Shenmen(HT7)/Shaohai(HT3)), as well as Taiyuan (LU9) of the lung meridian, increased significantly (P < 0.05). With regard to the metabolic features, rSO2 of the somatic site of the heart meridian (Shaohai (HT3)) in the CSAP group decreased significantly (P < 0.05) as compared to the healthy control group. The between-group difference in rSO2 in the lung and heart meridians (Taiyuan (LU9)/Chize (LU5)) and Shenmen (HT7), respectively, was not statistically significant. Conclusions Specific somatic sites in the heart meridian typically exhibit more significant changes in their microcirculatory, thermal, and metabolic characteristics than those in the lung meridian, thereby supporting the relative specificity for the visceral-somatic association in the disease state of CSAP. Trial registration: Clinicaltrials.gov (registration number: NCT04046640)